KEMAMPUAN MENULIS KARANGAN ARGUMENTASI DENGAN TEKNIK KONSTRUKTIVISME SISWA KELAS X SMA NEGERI 1 BASA AMPEK BALAI TAPAN - Yuningsih, Rahmadani; Mana, Lira Hayu Afdetis; Nisja, Indriani (Pendidikan Bahasa Indonesia, 2013)
This research is motivated by four phenomena, namely (1) techniques writing bervariaif not appear, (2) low ability students in developing the idea or ideas into an essay, and (3) interest and motivation of students is still low in writing.This study aimed to describe the argument essay writing skills with constructivism technique class X SMA Negeri 1 Basa Ampek Balai Tapan. This research is quantitative using descriptive method, which required a lot of research that uses numbers, ranging from data collection, interpretation of data, and as well as the appearance of the results.The subjects were students of class X SMA Negeri 1 Basa Ampek Balai Tapan. Samples were students of class X SMA Negeri 1 Basa Ampek Balai Tapan Â totaling 40 people. The data of this study aimed to test the students writing.Â Based on the results of the study concluded the following matters; First, the application of constructivism technique class X SMA Negeri 1 Basa Ampek Balai Tapan tongue quite well. Second, in general the average value of the argument essay writing skills class X SMA Negeri 1 Basa Ampek Balai Tapan is 73 with more than enough qualifications.Conclusions relevant to the study, recommended two things. First, the ability to write essays arguing tenth grade students of SMA Negeri 1 Basa Ampek Balai Tapan needs to be increased again. Second, the techniques should be utilized functionally constructivism in learning to write an argument essay.Â